Subsidies in Chilean Public Utilities - Serra, Pablo (World Bank, Washington, DC, 2015)
The author analyzes subsidies in Chile's public utilities. Over the last decade, especially, significant efforts have been made to extend public services to rural populations. An explicit consumption subsidy for potable water (targeted to the poorest twenty percent of the population) currently benefits seventeen percent of the population. Cross-subsidies have been virtually eliminated in Chile, and existing subsidies are funded from the national budget. The elimination of cross-subsidies has facilitated competition in some services. Prices have fallen substantially in services that new operators have entered, showing that regulation is a poor substitute for competition. The Chilean experience shows that it is possible to design direct subsidies (such as the one for drinking water) at relatively low cost to the state. Moreover, putting rural infrastructure projects out to public tender whenever possible, has allowed substantial reductions in government spending. Chile's experience also shows that it is possible to use subsidies that do not distort people's behavior - by making sure that they perceive the marginal cost of providing the service. In rural zones where there is no infrastructure, investment needs to be subsidized. Users do not pay the long-run marginal cost, but it is important that the rate charged, at least cover the short-term marginal cost. In other words, rural utility charges are required to cover the system's operating costs. For those who argue that the poor would be better off with cash transfers (choosing their own consumption baskets), the author outlines the arguments for subsidizing utilities, beyond the moral value of giving the poor access to public services, considered basic for existence.